Jamun (Syzygium cumini) seed and orange (Citrus sinensis) peel extracts ameliorates toxic effects of lead on kidney biomarkers in rats - Ram Prataap Yadav; Sunil Kumar Srivastav; Nobuo Suzuki; Ajai Kumar Srivastav (Acta Scientiarum. Animal Sciences, 2024)
Wistar rats were treated as Group A: Control; Group B: Lead (50 mg kg-1 b wt.); Group C: Lead (50 mg kg-1 b wt.) and jamun seed extract (JSE) (200 mg kg-1 b wt.); Group D: Lead (50 mg kg-1 b wt.) and orange peel extract (OPE) (200 mg kg-1 b wt.); Group E: OPE (200 mg kg-1 b wt.) and Group F: JSE (200 mg kg-1 b wt.). Serum urea, creatinine and serum uric acid levels were analyzed on days 7 and 14. Rats from Group B showed increased serum creatinine from days 7 to 14. Creatinine level decreased in group C and group D at days 7 and 14 as compared to group B. Increased serum urea was recorded in group B rats from 7 days. Rat from group C or group D showed decreased serum urea after days 7 day and 14 as compared to Group B. Lead exposure to rats provoked increased serum uric acid on days 7 and 14. Uric acid decreased in group C and group D on days 7 and 14 as compared to rats of group B. No alteration in creatinine, urea and uric acid level was seen in OPE and JSE treated rats at days 7 and 14.